تحسين فرصة الحصول على عطاء مشروع هندسي لأبنية مدرسية باستخدام الشبكات العصبيَة الصنعية - عمران جمال; نجا هاني; صوفان مي (Latakia University Journal -Engineering Sciences Series, 2019)
اهتم العديد من الباحثين بتطوير نماذج رياضية وإحصائية لتساعد المقاولين في تحديد نسبة الضم أو التنزيل التي تزيد من فرصة الفوز بالعطاء عند تقدمهم لمشروع ما, ولسوء الحظ فإنَ كثيراً من هذه النماذج لم تطبق وذلك إما بسبب النقص في المعلومات المطلوبة لتطبيق النموذج, وإما بسبب درجة التعقيد الكبيرة في تطبيق بعض تلك النماذج في الحياة العملية. ويقدم هذا البحث نموذج شبكة عصبية Neural Network تساعد المقاول في تحديد نسبة الضم أو التنزيل التي تزيد من فرصة فوزه بالعطاءات الخاصة بمشروعات تنفيذ المدارس. وقد تم تصميم وتدريب واختبار الشبكة بالاعتماد على 118 عينة من المشروعات المنفذة في قرى ومدن الساحل السوري, أما تحديد العوامل التي تؤثر على نسبة التنزيل أو الضم والتي تعتبر كدخل للشبكة فقد تم تحديدها بالاعتماد على استبيان تم توزيعه على عدد كبير من المقاولين العاملين في هذا النوع من المشروعات. وقد تم تدريب واختبار الشبكة على العينات المذكورة سابقاً من أجل معماريات مختلفة للشبكة وذلك لاختيار المعمارية التي توافق الخطأ الأصغري, وتبين أن الشبكة العصبية المكونة من طبقتين خفيتين تحوي كل منهما عشر عصبونات وباستخدام تابع التنشيط سييغمويد ومعدل تعلم 0.8 أعطت أفضل النتائج. A lot of researchers have developed many mathematical and statistical models to help the contractor to determine the mark up that increases the opportunity of winning a project bid. Unfortunately, most of these models were not applied in construction project bids, either because of the lack of required information or the complexity of applying some of these models in the practical life. This paper presents neural network model which can help the contractor determine the bid price that increases the opportunity of winning the bid of school construction project. The proposed neural network has been designed, trained and tested using 118 samples of school projects distributed in the villages and the cities of the Syrian coast. The factors affecting the bid price which are considered to be the network input, have been determined by the use of questionnaire distributed among many experienced constructors involved in this kind of projects. The network was trained and tasted for different architectures in order to choose the network architecture that leads to the minimum percentage of errors, and it came out that the network that consists of two hidden layers with ten neuroses in each hidden layer with sigmoid function and learning rate of 0.8 gave the best results.